MEAT PRODUCTIVITY OF FRENCH-BRED BULLS DUE TO ADAPTIVE TECHNOLOGY IN WESTERN SIBERIA - Olga M. Sheveleva; Aleksei A. Bakharev (Siberian Journal of Life Sciences and Agriculture, 2022)
The study of meat productivity of introduced cattle breeds in Western Siberia using adaptive technologies is of scientific and practical interest. We carried out the experiment on five cattle groups of Hereford, Limousin, Charolais, Aubrac and Salers bull calves. Furthermore, we determined the indicators of weight growth from birth to 18 months and meat productivity at the age of 18 months. At birth, live weight control was carried out at 3, 6, 9, 12, 15 and 18 months when weighing animals in the morning before feeding and watering. We studied meat productivity during the control slaughter of animals at the Yalutorovsky meat processing plant. Three heads from each group were slaughtered. The slaughter was carried out according to the Lenin All-Union Academy of Agricultural Sciences [VASKhNIL] method. The experimental material was processed by the method of variation statistics using the Microsoft Excel software application. Steers of French meat breeds surpass Hereford cattle breeds in terms of live weight and average daily growth. The carcass weight of Charolais animals is 329.5 kg, which is 75.3 kg more than in Hereford bulls, P≥0.999. The results of the chemical analysis indicate that the highest fat content is contained in the minced meat of Hereford bulls – 10.6%. Introduced cattle breeds, when bred under new conditions, showed a fairly high level of meat productivity, carcasses were obtained during slaughter, with an optimal ratio of tissues and chemical composition of carcasses, in terms of the yield of edible parts in the carcass and the meat content coefficient, they surpass the Hereford cattle breed. Thus, French meat breeds are promising for beef production in Western Siberia.